Bersama Menumbuhkembangkan UMKM Desa Kertarahayu - Fitri, Nur (Journal of Tourism and Creativity, 2022)
Abstrac Kertarahayu Village has very diverse potential, one of which is in the field of MSMEs. Micro, small and medium enterprises, commonly referred to as MSMEs, are business actors engaged in various business fields, which include the interests of the community. Kertarahayu Village has MSME products, one of which is in the food sector, which is already well known in several surrounding villages. Based on observations made by the UPI 107 KKN group, it's just that there is a problem that is a factor in the weak results of MSMEs in Kertarahayu Village, namely the packaging. The packaging development workshop provides knowledge and understanding to the community of the importance of developing MSMEs in this village. The result of this activity is that the community is also equipped with skills on how to design logos for packaging in order to create branding and high competitiveness. Keywords: Growing; MSME; Kertarahayu Village Abstrak Desa Kertarahayu memiliki potensi yang sangat beragam, salah satunya yaitu di bidang UMKM. Usaha mikro kecil dan menengah yang biasa disebut UMKM merupakan pelaku bisnis yang bergerak pada berbagai bidang usaha, yang mencakup kepentingan masyarakat. Desa Kertarahayu memiliki produk UMKM salah satunya yaitu dibidang makanan, yang sudah terkenal dibeberapa desa sekitar. Berdasarkan observasi yang dilakukan oleh kelompok KKN UPI 107 hanya saja terdapat suatu permasalahan yang menjadi faktor lemahnya hasil UMKM di Desa Kertarahayu ini, yaitu pada kemasannya. Dari kegiatan lokakarya pengembangan kemasan memberikan pengetahuan dan pemahaman kepada masyarakat pentingnya menumbuhkembangkan UMKM yang ada didesa ini. Hasil dari kegiatan ini juga masyarakat dibekali keterampilan bagaimana mendesain logo untuk kemasan agar menciptkan branding dan daya saing yang tinggi. Kata Kunci : Menumbuhkembangkan; UMKM; dan Desa Kertarahayu